COVID-19 is still here: Discussing home-based online assessments - Asiah, Kassim (Penerbit Universiti Malaysia Pahang, 2021)
At present, assessments which are part and parcel of the teaching and learning process, have gone through leaps and bounds transiting from the conventional face-to-face setting to home-based online platforms as a consequence of the COVID-19 pandemic that is still looming worldwide after more than a year from its first hit. This move is made possible with technology support that has been integrated in all language assessments of different skills. This editorial section previews some issues discussed in literature in relation to the assessments conducted online on four language skills – listening, reading, speaking and writing. The discussion attempts to relate the use of varied digital means and technological aids to the efficacy of the assessments’ constructs in light of their benefits and challenges faced in the transition and administration phases. The section concludes with the call for collaboration between language practitioners and researchers on a platform where ideas and knowledge can be exchanged and eventually implemented in language classes and assessments to facilitate the enhancement of learners learning experience and achievements.